Flowering, fruiting, seed germination and seedling growth of Macaranga gigantea - DWI SUSANTO; DADDY RUCHIYAT; MAMAN SUTISNA; RUDIANTO AMIRTA (Biodiversitas Journal of Biological Diversity, 2016)
Susanto D, Ruchiyat D, Sutisna M, Amirta R. Flowering, fruiting, seed germination and seedling growth of Macaranga gigantea. Biodiversitas 17: 192-199. The stages of flower and fruit development of Macaranga gigantea, its seed germination behavior in nature and from fruit harvesting, as well as the process of raising its seedlings in the laboratory were studied to determine the potential for production of M. gigantea seedlings. Five reproductive trees of M. gigantea were chosen as sources of seed. To estimate natural germination rates, four sample plots of 1 x 1 m 2in four cardinal directions below the crown of every tree were set up. In addition, dry and wet extraction processes were carried out to determine, which the more effective method for germination of M. gigantea seeds. The results showed that the time required from flower development to fruit ripening in M. gigantea flowers was 5-6 months. The flower buds initiated in the dry season (August 2011). The germination in laboratory showed that the percentage and the rate of germination of the seeds extracted through the wet extraction process were higher than those extracted through the dry extraction process. The highest rate of germination planted on mushroom spawn waste media was the highest rate (0.36 0.42%), followed by those planted on compost media (0.150.09%), top soil media (0.100.04%) and sand media (0.100.07%).